The Concept of Dissimilation in the Study of Inter-ethnic Marriages within Homogeneous Meskhetian Turkish, Azerbaijani Marriages in Turkestan - Abdinassir, Nazira (Ethnographica et Folkloristica Carpathica, 2024)
While analyzing the preservation of cultural heritage is more straightforward in homogenous households, inter-ethnic marriages present a captivating lens through which to examine cultural integration, social identity, and the preservation of tradition within diverse societies. This study explores the dynamics of inter-ethnic and homogeneous marriages among Meskhetian Turks and Azerbaijanis in Kazakhstan, applying the theoretical framework of dissimilation theory. By drawing on fieldwork conducted in 2024 which involved 45 interviews from two research villages, Turki Poselkasy and Kentau, located in the Turkestan province in the southern part of Kazakhstan, the research investigates the historical context and contemporary realities faced by these communities. In doing so, it highlights differences in culture, language, ​​and social norms that can influence the formation of both mixed and homogeneous marriages among minority groups in the region. The theoretical background of the study is grounded in dissimilation theory, which posits that individuals in inter-ethnic marriages tend to distance themselves from their own ethnic groups to establish new identities within the context of their relationships. Through interviews and surveys conducted across diverse settlements, the study explores social identities and groups as well as concepts of cultural and social differences including gender dynamics, to uncover the intricate mechanisms of dissimilation.